Tarekat Qadiriyah wa Naqsyabandiyah di Banjarmasin: Perjalanan Spiritual Islam Sufi di Kalimantan Selatan - Fadhel Muhammad; Muhammad Rivaldi Akbar; Muhammad Ridwan (Forum for Social and Humanities Studies, 2026)
The Tariqa of Qadiriyah wa Naqsyabandiyah (TQN) is a conbination of two major Sufi orders, the Tariqa of Qadiriyah and the Tariqa of Naqsyabandiyah, combined by a great Nusantara Sufi scholar, Shaykh Ahmad Khatib Ibn Abdul Ghaffar al-Sambasi al-Jawi (d. 1878 CE), who resided in Mecca until the end of his life. This study aims to explore the spiritual journey of Sufis who practice the Tariqa of Qadiriyah wa Naqsyabandiyah and its influence on the community of Banjarmasin, South Kalimantan. The method employed is the historical method through the stages of heuristics (source collection), criticism (source verification), interpretation, and historiography (historical writing). Research sources were obtained from books, scholarly articles in accredited national journals, and other sources relevant to the discussed topic. The reading materials include books and articles discussing the Tariqa of Qadiriyah wa Naqsyabandiyah and its development in the Nusantara, particularly in South Kalimantan. This study reveals that theTariqa of  Qadiriyah wa Naqsyabandiyah entered South Kalimantan through the efforts of Prof. Dr. H. M. Zurkani Yahya in 1998, who was a deputy talqin (authorized representative for initiating disciples) from Suryalaya Islamic Boarding School. After the passing of Prof. Zurkani Yahya, his successor as the deputy talqin continuing the teachings of TQN in South Kalimantan was Drs. K.H. Syakrani Nasri. This Sufi order not only brought spiritual teachings but also played a role in addressing social issues such as juvenile delinquency and drug abuse through Pondok Inabah, which utilizes TQN dhikr (remembrance of God) methods as spiritual therapy. Although Pondok Inabah Banua Anyar is currently inactive, guidance continues under the leadership of the Deputy Talqin. The Tariqa of Qadiriyah wa Naqsyabandiyah continue to play a role in providing explanations, understanding, and the talqin dhikr to the community in South Kalimantan, with the primary goal of drawing closer to Allah SWT; social impacts, such as spiritual healing, are effects of these dhikr practices.